2008
DOI: 10.1523/jneurosci.1480-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the β-Adrenoceptor–Protein Kinase A Signaling Pathway within the Ventral Bed Nucleus of the Stria Terminalis Mediates the Negative Affective Component of Pain in Rats

Abstract: Pain is an unpleasant sensory and emotional experience. The neural systems underlying the sensory component of pain have been studied extensively, but we are only beginning to understand those underlying its affective component. The bed nucleus of the stria terminalis (BNST) has been implicated in stress responses and negative affective states, such as anxiety, fear, and aversion. Recently, we demonstrated the crucial role of the BNST in the negative affective component of pain using the conditioned place aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 21 publications
1
64
0
Order By: Relevance
“…Such neural connectivity provides a route by which contextual information encoded by the HPF could bypass the BLA and activate the vPAG to generate freezing. Conversely, the BST is capable of receiving noxious information (i.e., footshock) both directly and indirectly (37,38). Consistent with this hypothesis, lesions or inactivations of the BST result in a wide range of fear-and anxiety-related deficits (39)(40)(41)(42).…”
mentioning
confidence: 67%
“…Such neural connectivity provides a route by which contextual information encoded by the HPF could bypass the BLA and activate the vPAG to generate freezing. Conversely, the BST is capable of receiving noxious information (i.e., footshock) both directly and indirectly (37,38). Consistent with this hypothesis, lesions or inactivations of the BST result in a wide range of fear-and anxiety-related deficits (39)(40)(41)(42).…”
mentioning
confidence: 67%
“…β-Adrenergic receptors are closely related to opioids (12), and the β 1 -adrenergic receptor is reported to be especially involved in the negative affective component of pain (14). The A145G SNP (rs1801252) causes an amino acid substitution.…”
Section: A145g Snpmentioning
confidence: 99%
“…The BNST also reportedly plays an important role in the generation of the negative affective component of pain and is densely innervated by noradrenergic fibers (13). A report that examined the role of noradrenergic transmission within the BNST found that an intra-ventral BNST injection of the β-adrenergic antagonist timolol dose-dependently attenuated intraplantar formalin-induced conditioned place aversion without reducing nociceptive behaviors (14). Thus, β-adrenergic receptors, whose involvement in the negative affective component of pain has been demonstrated, are also considered likely to affect pain sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…To date, lesions (reversible or irreversible) or pharmacological manipulations of the BST suggest roles in the physiology of fear, food intake, social behaviours, pain, and goal-directed behaviours and the associated pathophysiological states such as anxiety, anorexia, and addiction (Ciccocioppo et al, 2003;Colussi-Mas et al, 2005;Crown et al, 2000;Delfs et al, 2000;Deyama et al, 2007Deyama et al, , 2008Deyama et al, , 2009Dumont et al, 2005;Dunn and Williams, 1995;Epping-Jordan et al, 1998;Erb and Stewart,1999;Fendt et al, 2003;Gewirtz et al,1998;Jasnow et al, 2004;Lee and Davis, 1997;Leri et al, 2002;Liu et al, 2009;Nakagawa et al, 2005;Sajdyk et al, 2008;Sullivan et al, 2004;Walker and Davis, 1997;Walker et al, 2000;Wang et al, 2001). …”
mentioning
confidence: 99%